The foreign experience in training public procurement specialists on the example of the USA, Great Britain and China - V. A. Tsibikov (Управление)
The article reveals the features of the training of specialists in public procurement in countries with different types of economies and forms of state power in terms of the training system, applied pedagogical forms, methods and tools. The training programs for training foreign educational institutions, which are characterized by sufficient variability and adaptability in accordance with the needs of students, the intensity of the use of various forms of training: full-time (classroom), distance (in the mode of video conferencing during webinars), as well as by sending educational material and monitoring performance via email have been analyzed. The content of other educational documents and official publications in the media, as well as the results of correspondence (through chatting and e-mail) with representatives of training courses and leading training centers, answers to information requests to state authorities responsible for functioning contract system, – have been taken into account.Based on the results of the analysis, the following key positions, allowing us to observe fundamental differences in the training of public procurement specialists in the West and East countries: the degree of state participation in the regulation of the training system and the degree of severity of the educational function in the formation of the necessary level of legal awareness of procurement specialists have been highlighted. It has been established, that in the United States and Great Britain, private licensed organizations compete with each other in providing such educational services to those involved in the training of public procurement specialists. In China, due to the presence of problems in the fight against corruption in the actions of state customers, the closest attention is paid to the formation of the necessary personality traits of officials to minimize the risks of committing offenses in contractual legal relations.